Inughuit Nipaan: The Future of Archaeological Partnerships in Avanersuaq - Kleist, Mari; Walls, Matthew; Sadorana, Genoveva; Simigaq, Otto; Peary, Aleqatsiaq (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2022)
Inuit across the Arctic regions have for generations echoed a wish for a greater involvement in research and have voiced the need for direct partnerships that include Indigenous perspectives. As a consequence, researchers are becoming increasingly aware that studying other people’s past and heritage is not an inherent academic right but rather involves developing close Indigenous partnerships. Accordingly, partnership research frameworks are now being recognized as essential foundations to decolonize research practices in the Arctic, as vocalized by Inuit communities. In this paper, Inughuit community members share their personal and shared thoughts and reflections and present how they envision future partnership research approaches, how they can determine the objectives of partnered research, and what archaeology can ultimately contribute in a changing Arctic.